A review on the pathogenic bacterium Nocardia seriolae: aetiology, pathogenesis, diagnosis and vaccine development. (5th May 2022) - Liu, Yansheng; Chen, Guoquan; Xia, Liqun; Lu, Yishan
Abstract: Nocardia seriolae, a gram‐positive branching filamentous bacterium, is the causative agent of fish nocardiosis. It mainly infects fish through gills, anus, lateral line or surface injury, resulting in a large number of white nodules in visceral organs and skin ulcerations. N. seriolae can infect about 42 species of fish and severely harm the aquaculture industry in many regions, particularly in Asia. Aiming to have a more comprehensive understanding about N. seriolae, the literature of N. seriolae before January 2022 was collected by searching nine databases and the current knowledge of the host diversity, drug resistance, genotype and phenotype, virulence factor, molecular detection and vaccine development of N. seriolae was summarized in this review. The future studies of N. seriolae are also prospected in order to help the research on the pathogenic mechanism and control of N. seriolae infection .